Marketing systems for fish from Lake Tana, Ethiopia: Opportunities for marketing and livelihoods - Gordon, A.; Demissie, S.; Tadesse, M. (International Livestock Research Institute, 2007)
This report concerns the domestic trade in frozen fish sources from Lake Tana in Ethiopia. During the initial participatory rural appraisal (PRA), fish was identified as a commodity with market potential in one of IPMS's (Improving Productivity and Market Success of Ethiopian farmers project). eight pilot learning woredas (PLW), namely Fogera woreda on Lake Tana. ILRI invited WorldFish Center to provide inputs to IPMS in support of the fisheries-related work. From a marketing perspective, two main fish products were noted, as well as local consumption of fresh fish in the fishing communities: dried catfish, from the lake and the ponds, destined for Sudan and markets in northern Ethiopia and frozen fish (mostly lake barbus and tilapia), distributed largely to Addis Ababa, though some serves the restaurant/hotel trade in Bahir Dar on Lake Tana (and to a lesser extent, Gondar). This study focuses on the frozen fish market chain for fish produced in Fogera woreda. In addition, in the margins of the main study, it was suggested that a preliminary assessment be made of the potential importance of the dried catfish trade. It assesses the Addis Ababa market for frozen fish; describes and analyses the frozen fish production and marketing system, for fish originating from Lake Tana, in particular from Fogera woreda; identifies constraints to and makes recommendations for further develop the frozen fish trade originating from Lake Tana; and makes a preliminary assessment of the potential importance of the dried catfish trade.